Bugden, Ruth. Photograph of a man, a women, and a woman holding a baby in front of a fence from Ruth Bugden's personal photograph collection part two. - Jarvis, Dale (1945)
Back of photograph of Fred Allen, Elizabeth Picco, Ruth Bugden, and Lily Allen on Witch Hazel Road.